Design of a low-voltage input-output rail-to-rail CMOS buffer - Pua, Poo Toong. (2009)
Scaling of modern integrated circuit (IC) technologies as well as the increasing important of battery and solar powered system, demand more and more circuit to be able to operate at very low supply voltage environments. The most important basic building block in analog and mixed-mode circuits is the operational amplifier and buffer. In this report, a low voltage quasi rail-to-rail opamp input is introduced. A common-mode adapter that uses the common-mode voltage present at the common-source node of the available differential pair to accommodate the large common-mode input signal is proposed. The output stage of buffer uses a rail-to-rail class-AB with simple folded mesh feedback control without any resistors. The design of the buffer in this project is based on AMIS 0.5μm CMOS technology. The finalized buffer operates at 1.5V supply voltage and allows rail-to-rail input and output swings.